Housing liquidity, mobility, and the labour market - Allen Head; Huw Lloyd-Ellis (Queen's University, Department of Economics, 2009)
The relationships among geographical mobility, unemployment and the value of owner-occupied housing are studied in an economy with heterogeneous locations and search frictions in the markets for both labour and houses. Differences in labour market conditions between cities affect the speed with which houses may be sold - that is, the liquidity of housing. At the same time housing market conditions affect employment decisions and thus the allocation of labour across cities. In equilibrium, unemployment rates for home-owners are higher than for otherwise identical renters. Unemployment and home-ownership rates are, however, negatively correlated across cities. In a parameterized example we find that, although renters are much more mobile than owners, the impact of home-ownership on aggregate unemployment is quantitatively small.
Keywords: J61; J64; R23; 330; liquidity; mobility; home-ownership; unemployment; Arbeitsmarkt; Arbeitslosigkeit; Arbeitsmobilität; Grundbesitz; Verkauf; Theorie